Women, Healthcare, and Health Technology in Finland - Hupa, Elisa (My University, 2024)
The digital era has effected numerous changes in medicine and healthcare. One example thereof is MedTech, which refers to all types of medicotechnological innovations and devices. The Finnish MedTech industry is worth over 1.27 billion USD and is rapidly growing. FemTech is a subcategory of MedTech, defined as such technological innovations which improve women’s health or healthcare. FemTech, also, is a rapidly growing industry, with strong roots in Finnish medical innovations. For example, the hormonal IUD is a Finnish invention with millions of users worldwide. There is a distinct difference in the perceived and measured health of men and women in Finland. Women are, on average, healthier and live longer, but women use healthcare services more frequently and have a stronger decline in health in older age. From a global perspective, women are distinctly unhealthier than men – both in industrial countries and in developing countries. In addition, globally, all the social, cultural, economic, and biological factors which affect health, affect the health of women to larger degree than they affect the health of men. Therefore, for any gender, it is important to view a person’s situation from a broader vantage point – besides gender, a person’s health is affected by their socioeconomic status and wealth, their ethnicity, their age, and generation and so on. The social repercussions of declined health are not equal between the genders either. Thus, it is not sufficient to compare health conditions or diseases between the genders, but rather it is crucial also to consider other factors which impact on how a person will experience their health condition. This kind of perspective is called intersectionality, a sociological framework, and it is applicable in many ways in healthcare as well.
Keywords: naisten terveys, terveydenhuolto, terveysteknologia, FemTech, MedTech, sukupuolten väliset terveyserot